Synthesis and characterization of novel organo-montmorillonites - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Applied Clay Science, 2008)
Sodium Montmorillonite (NaMMT) has been modified via cation exchange reaction using three different organic cations. Basal spacings, interlamellar structure and thermal stability of these organo-montmorillonites (OMMT) clays have been characterized using wide angle X-ray diffraction (WARD) and thermogravimetric analysis (TGA) techniques. Increase in the basal spacing due to organic modification is in good agreement with simple theoretical calculations based on van der Waals volume of the cationic ammonium ions. TGA characterization and analysis show that the amount of organic modifier in the OMMT's is in good agreement with theoretically calculated stoichiometric content expected for almost complete exchange of Na+ ions by organic cations. The OMMT's shows stepwise decomposition corresponding to initial weight loss from residual water desorption, followed by decomposition of the organic surfactant and the dehydroxylation of structural water of the montmorillonite layers. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Montmorillonite; organo-clays; organo-montmorillonite; surfactant